Spiritual Leadership of Teacher at Islamic Boarding School Darul Kamal An-Nur NW Kembang Kerang: In the Study of Islamic Education Management - Adindi, Satria; Arifin, Zainal; Subiyantoro (Universitas Negeri Jakarta, 2024)
Background The concept of spiritual leadership of the spiritual leader is one of the efforts to overcome various crises, including the moral crisis of students, as well as the leadership crisis in the 21st century. Purpose This research is important to understand the spiritual leadership of Tuan Guru at the Darul Kamal An-Nur NW Kembang Kerang Islamic Boarding School in the context of Islamic education management. Design/method/approach The method used is descriptive qualitative with primary and secondary data. Primary data was obtained through observations, documentation, and interviews. In contrast, secondary data came from scientific journals, documents, and other sources related to spiritual leadership in the study of Islamic education management. Results The results show that Tuan Guru's spiritual leadership emphasizes creating an organizational environment based on love, empathy, faith, and purity. The crisis of leadership and the decline in students' character can be addressed through spiritual leadership, character education, and motivation. The Focus of Tuan Guru's spiritual leadership at the Darul Kamal An-Nur NW Kembang Kerang Islamic boarding school is the formation of student character and motivation, and the harmonious relationship between teachers, students, parents, and the wider community. Contribution/value This concept illustrates how the spiritual leadership pattern of Tuan Guru shapes the character of students, their learning motivation, and the solidarity among teachers.